Emotion-Specific Affective Theory of Mind Impairment in Parkinson's Disease. Issue 1 (December 2018) - Yu, Rwei-Ling; Chen, Po See; Tu, Shao-Ching; Tsao, Wei-Chia; Tan, Chun-Hsiang
Abstract The neuropathology of Parkinson's disease (PD) involves the frontal-subcortical circuit, an area responsible for processing affective theory of mind (ToM). Patients with PD are expected to experience deficits in the affective ToM. This study aims to investigate whether the ability to infer emotion in others is affected in either young-onset Parkinson's disease (YOPD) or middle-onset PD (MOPD) patients and to test whether the impairments in affective ToM are associated with the motor symptoms. The affective ToM, global mental abilities, and clinical symptoms were assessed in a total of 107 MOPD, 30 YOPD, and 30 normal controls (NCs). The MOPD patients exhibited deficits in affective ToM to the negative and neutral valences, when compared to the participants in the NCs and YOPD group. By conducting gender-stratified analysis, the deficits in affective ToM was only found in female participants. After adjusting for demographic variables, the multiple linear regression model revealed that affective ToM predicted motor symptoms, especially in female MOPD patients. The present study may aid in the development of medical care programs by advocating for a more comprehensive therapeutic plan that includes continuous disease progression monitoring and social skills training for female MOPD patients or their caregivers.